MODERN VIEW ON THE LONG ACTING β2-AGONISTS IN THERAPY FOR THE BRONCHIAL ASTHMA AMONG CHILDREN - Yu.G. Levina; L.S. Namazova (Педиатрическая фармакология)
The article deals with the long acting β2-agonists in therapy of children, suffering from the bronchial asthma, with regards to the recommendations of the modern manuals. Inhalant long acting β2-agonists, which formoterol and salmeterol belong to, are applied in combination with the inhalatory glucocorticosteroids among the patients with poor control asthma at inhalatory glucocorticosteroids based monotherapy.Key words: long acting β2-agonists, formoterol, salmeterol, bronchial asthma, children.